Analisis Implementasi Khiyar pada Bisnis E-Commerce dalam Perspektif Hukum Islam (Studi Kasus pada Toko Online Sale Stock Indonesia) - Muhsin Hariyanto; Irma Khoiriyah (Syntax Idea)
This research aimed to analyze the implementation of khiyar on e-commerce business in Sale Stock online store Indonesia. Khiyar is the right to decide for both sellers and buyers to proceed or cancel the sale and purchase agreement. This research was a field research using qualitative approach. The data were collected through participant observation in which the researcher was also involved and became part of the source of data. The data were also collected through interview and documentation. The interview was conducted to some customers who once returned the product to Sale Stock online store Indonesia and also to the customer service of Sale Stock Indonesia. Based on the research, it could be concluded that e-commerce business on Sale Stock online store Indonesia implemented khiyar, that were khiyar majlis, khiyar aib, khiyar syarat, khiyar sifat, khiyar ta’yin, khiyar ru’yah, and khiyar naqd.